2018
DOI: 10.1177/0300060518773223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between loneliness and medication adherence in patients with diabetes mellitus: A cross-sectional study

Abstract: ObjectiveThe emotional status of patients with diabetes mellitus (DM) is important in the course of treatment. The present study aimed to determine the level of loneliness among patients with DM and to evaluate the relationship between the patients’ level of loneliness and medication adherence.MethodThis cross-sectional study used a semi-structured questionnaire and the University of California, Los Angeles Loneliness Scale to collect data from 325 patients who were diagnosed with DM.ResultsWe found that lonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 25 publications
4
24
5
1
Order By: Relevance
“…An assessment of the relationship between loneliness and treatment adherence in diabetic patients showed a correlation between loneliness and postprandial blood glucose levels in these patients. Similarly to our study, no correlation was shown between HbA1c and BMI [ 21 ]. Also, no relationship was demonstrated between loneliness and these indicators in a study assessing the severity of already impaired response to stress in T2DM patients [ 14 ].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…An assessment of the relationship between loneliness and treatment adherence in diabetic patients showed a correlation between loneliness and postprandial blood glucose levels in these patients. Similarly to our study, no correlation was shown between HbA1c and BMI [ 21 ]. Also, no relationship was demonstrated between loneliness and these indicators in a study assessing the severity of already impaired response to stress in T2DM patients [ 14 ].…”
Section: Discussionsupporting
confidence: 79%
“…We assessed the relationships between loneliness and metabolic control indicators. Available studies indicate that HbA1c and BMI were the most common metabolic control indicators assessed in relation to loneliness [ 12 , 14 , 21 , 22 ]. An assessment of the relationship between loneliness and treatment adherence in diabetic patients showed a correlation between loneliness and postprandial blood glucose levels in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6–9 Third, previous studies have linked loneliness to the failure to engage in a range of health/preventive behaviours including lower adherence to a healthy diet, 30 and medical non-adherence. 15 , 16 Importantly, the results of this study build on the findings of a recent Japanese study that looked at factors associated with not social distancing, 20 by not only indicating that loneliness may be prevalent in Japan in the early stages of the pandemic, but by showing that it is also associated with non-adherence to COVID-19 preventive behaviours. In addition, our results also accord with those of a recent study from Poland which tentatively suggested a negative link between loneliness and the use of COVID-19 preventive strategies.…”
Section: Discussionsupporting
confidence: 67%
“…Recent research has linked worse psychological health (anxiety, depression) to poorer COVID-19 preventive behaviours, 14 while earlier studies have shown an association between loneliness and lower medical adherence. 15 , 16 Importantly, a recent study from Poland has indicated that loneliness may be negatively linked to COVID-19 preventive behaviours but that study did not examine the relation with individual preventive behaviours. 12 Although it is uncertain how loneliness might be associated with preventive behaviours several pathways might be involved.…”
Section: Introductionmentioning
confidence: 99%